Pemberdayaan Ibu Rumah Tangga melalui Pelatihan Pembuatan Kerajinan Tangan di Dusun Citeureup - Sherlly Syah Putri; Vita Aprilina; Yuha Nadhirah Qintharah (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
The amount of free time that housewives have in Dusun Citeureup I is often not used properly so they are said to be less productive. Empowerment of housewives will encourage increased productivity and the potential for the formation of new businesses which have implications for improving the economy, especially the family economy. The community service program for empowering housewives is training to make handicrafts from used bottle caps and making bohemian bags. The method of implementing this program uses community education and training. The stages of the activities carried out were conducting counseling, training, and mentoring in making handicrafts from used bottle caps and making bohemian bags. This activity is said to be a success because of the high enthusiasm of housewives to attend the event and their interest in trying to learn to make bohemian bags and other handicrafts from used bottle caps. From the two trainings, the interest in making bohemian bags became superior as evidenced by the request from the Chair of Family Empowerment and Welfare to be taught privately. Making bohemian bags and handicrafts from bottle caps can be done in free time so as not to interfere with household work so as to minimize unproductive free time. The results of this craft can also be sold so that it can increase income and improve the family's economy. This craft requires patience, patience, and innovation, and still needs assistance for training.